Penguatan Eduwisata Hidroponik Barokah dan Inovasi Produk Sayur - Amraini Amelia; Chindiana Khutami; Adria Wuri Lastari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program was conducted at the Barokah Hydroponic Group in Kenali Asam Atas Subdistrict, Jambi City, which operates an active hydroponic system but has not yet optimally utilized it as educational tourism or a source of value-added product development. The main challenges faced by the partner included the absence of durable processed vegetable products and the lack of standardized educational tourism management. This program aimed to strengthen hydroponic educational tourism and develop innovative vegetable-based processed products in the form of vegetable powder (simplisia) to enhance community capacity and economic potential. The implementation methods included preparation, socialization, training, application of simple technology, mentoring, and evaluation. Activities focused on producing vegetable powder from Brazilian spinach and common spinach, developing Standard Operating Procedures (SOP) for educational tourism, and providing initial mentoring for educational tourism implementation. The results indicated an improvement in partners’ knowledge and skills, as reflected by an increase in average pre-test scores from 60% to 82% in the post-test. In addition, the partners successfully produced value-added products and established structured guidelines for managing educational tourism activities. This program is important as a sustainable model for strengthening hydroponic-based educational tourism and local product innovation